Power and Status in the Roman Empire, AD 193-284 - Mennen, Inge (Impact of Empire, 2011)
This book deals with changing power and status relations between AD 193 and 284, when the Empire came under tremendous pressure, and presents new insights into the diachronic development of imperial administration and socio-political hierarchies between the second and fourth centuries. Readership: All those interested in the socio-political history of the ancient world, the workings of Roman imperial administration, and the connections between center and periphery within the Roman Empire.